TINJAUAN LITERATUR SISTEMATIS : PENGARUH ICE BREAKING TERHADAP KONSENTRASI DAN MINAT BELAJAR SISWA SEKOLAH DASAR - Christyowati, Yunitha Ike; Dewi, Noorwindhi Kartika (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
This research delves into the effects of ice-breaking on the concentration and interest in study among elementary school children, underscoring that livelier and hands-on strategies can improve academic interest and attention. By studying trends, patterns, and effective pedagogical methods through a systematic review of existing research, the study seeks to establish a dynamic, stimulating learning environment that significantly improves the quality of primary education. Using the Systematic literature review (SLR) approach, this study collates data through the gathering, analysis and synthesis of the literature based on empirical research directly related to ice-breaking activities on elementary students' concentration and learning interest and utilizes literature from a mixture of academic databases such as Google Scholar and Science Direct with PRISMA screening applied and followed up with the content analysis to source patterns from trends that can help in evidence-based practices in education. The study concluded that ice-breaking activities play vital role in enhancing concentration, motivation and learners' engagement in the learning process. An application of systematic review allowed for the verification of findings, noting that interactive and physical activities seem to have the highest impact. Such techniques have reduced anxiety and enhanced a positive learning environment while building stronger teacher-student relationships essential to student achievement. In conclusion, the study highlights the significance of adhering ice breaking activities in the high education system to improve the quality of education.